Performing: Hotel room attendants' employment experiences. (January 2016) - Kensbock, Sandra; Jennings, Gayle; Bailey, Janis; Patiar, Anoop
Highlights: Adopting a socialist-feminist and critical theory standpoint to tourism studies. Highlights the low status and denigration of room attendants. Adopting a constructivist grounded theory methodological approach. Gives 'voice' for room attendants to be recognized as a community of value. Demonstrates that room attendants have significant impact on guests' experiences. Abstract: Performing is a socio-psychological process of defining self as a room attendant and finding dignity in the course of completing daily tasks while interacting with other social actors—guests and hotel employees—on hotel stages. The grounded theory of performing emerged from qualitative research, informed by socialist-feminist critical theory and qualitative social constructivist grounded theory. Forty-six room attendants working in one of five participating 5-star hotels located in South East Queensland, Australia, were interviewed. Performing has ramifications for tourism service provision, specifically, hotel praxis and the need for greater acknowledgement of room attendants as a community of value, possessing practical knowledge that could be used to improve daily operations, enhancing guest interactions and tourism service experiences.